Controle de vibrações em máquinas rotativas utilizando atuadores eletromagnéticos - Koroishi, Edson Hideki (2013)
The aim of the present work is the study of active vibration control of flexible rotors using electromagnetic actuators. For this purpose, a flexible rotor was considered and modeled by using the Finite Element Method. As the original rotor model presents a high number of degrees of freedom, the Pseudo-Modal Method was used for reducing the size of the model. The design of the controllers used two different approaches. The architecture of the first one is based on the H∞ norm and Optimal Control, so that both methods were developed by using Linear Matrix Inequalities. The advantage of the LMIs is that they are able to take into account parameter uncertainties. In the second approach, the architecture of the controllers was developed by using Fuzzy Logic techniques. In these two approaches the controllers were designed in the modal domain. The advantage of the modal contol is that the controllers can be designed using small number vibration modes of the system, thus contributing to reduce the computational cost. In the modal control, the modal states are not directly accessible from the experiment. For determining the mode estimates, the Kalman estimation technique (Kalman Filter) was employed. The advantage of this estimator is its ability in determining the modes from noisy signals. Regarding the electromagnetic actuators, they have nonlinear behavior; the corresponding nonlinear problem is solved by using the inverse model of the actuators. The developed methodology was analyzed both numerically and experimentally.The performance of the controllers was tested under several conditions for the operation of the rotor. The obtained results, both numerical and experimental, demonstrate the success of the methodology conveyed and its great potential for the active vibration control of flexible rotors, in the context of the so-called smart rotors.